2021
DOI: 10.1186/s12935-021-02242-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of tertiary lymphoid structures in breast cancer prognosis: a systematic review and meta-analysis

Abstract: Background Tertiary lymphoid structures (TLSs), organizationally resemble lymph nodes, are frequently present in breast cancer (BCa). It is usually, but not always, associated with a positive prognosis or immunotherapy response in cancer patients. This meta-analysis was performed to assess the prognostic and clinical impact of TLSs in BCa. Methods We conducted a systematic search in PubMed, Embase, Cochrane Library, Web of Science, China National K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
(91 reference statements)
0
25
1
Order By: Relevance
“…A layered effect was observed, reminiscent of an “Inside-out lymph node” consisting of cytolytic CD8 + T cells surrounded by separate layers of CD4 + T cells and B cells. Recently, tertiary lymphoid structures (TLS) have been detected in tumors, which correlate with improved survival (40, 41). This configuration suggests an orthogonality in the lymphoid population that is like lymph node structures.…”
Section: Discussionmentioning
confidence: 99%
“…A layered effect was observed, reminiscent of an “Inside-out lymph node” consisting of cytolytic CD8 + T cells surrounded by separate layers of CD4 + T cells and B cells. Recently, tertiary lymphoid structures (TLS) have been detected in tumors, which correlate with improved survival (40, 41). This configuration suggests an orthogonality in the lymphoid population that is like lymph node structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous meta-analysis by Zhang et al. suggested that TLSs were related to better prognosis, their result was based on a limited number of studies, with only two or three studies providing survival outcomes ( 9 ). Furthermore, all included studies in their meta-analysis showed that TLSs were beneficial for prognosis, but opposite conclusions have been reported in the recent study ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a meta-analysis assessed the prognostic value of TLSs and their correlation with clinicopathological features, gene expression, and survival in all BC subtypes. A higher density of TLSs was reported to be significantly correlated with better DFS in all subtypes (HR = 0.40, 95% CI: 0.17−0.93, p < 0.001) [56].…”
Section: Tertiary Lymphoid Structuresmentioning
confidence: 92%